HUBUNGAN INTENSITAS PENGGUNAAN GADGET DENGAN KETERLAMBATAN PERKEMBANGAN PADA ASPEK BICARA DAN BAHASA PADA BALITA DI KELURAHAN TAMBAKREJO SURABAYA - Aula Nurmasari, NIM011211231026 (2016)
Gadget is a technological development that can cause addiction to its users, including toddlers. When using gadgets, toodlers become less interact and communicate. This can cause children to have delay development in speech and language. There were increased number of toddlers suffer from developmental problems during 2013 to mid-2015, based on Growth and Development Early Detection (DDTK) examination at Tambakrejo public health center. The purpose of this study was to analyze association between the intensity of gadgets use and delayed development in regard of speech and language aspects in Tambakrejo, Surabaya. This research used analytic cross-sectional method. Sample were taken from children aged 24-60 months in Tambakrejo Surabaya, who met the inclusion and exclusion criteria. Sampling method used was purposive sampling, with samples size as many as 163 respondents. Independent variable was the intensity of gadget use and dependent variable were speech and language development aspect. Researh instrumen used were questionnaire and KPSP. Data analysis method employed was chi square test ( = 0.05) and cramer’s v test was employed to analyze the association between two variables. Statistical analysis showed p value 0.000 (p value < 0,05) and correlation coefficient 0,346, which mean there was a significant correlation between the intensity of gadget use with speech and language development aspects but with a weak correlation. It was importent to give an educational games and supervise children during their play time.